(3JWHjbGJ GdGfJQfJs (3JYde LGaG ScQjHJs - (3SdGeI(B, (3MSjf GMeOs ((3YeGfs (3ecJHI GdeLJeY GdYQHjs, 2003)
(3aj gPG GdcJGH GdJUfja GdWHbj CSGSjGJ aj LGaG ScQjHJ , LOhd GdGfeGW GdeJYGbHI , (Bjava applets (3, HQJhcdGJ WHbI Gdfbd , (BROUTERS (3, cjGfGJ LGaG ScQjHJ , JYdjeGJ LGaG ScQjHJ ; fJGL (BHTML (3, GdeJZjQGJ , Gdbje GdMQajI , GdJMhjd Hjf CfhGY Gdbje, GdeLehYGJ GdeQJHI , GYdGf GdeLehYGJ GdeQJHI ; Led GSJOYGA GdhXGFa , OeL LGaG ScQjHJ eY (BHTML(3, eYGdLI GdfU GdHQeLj , gjcd HQfGeL LGaG ScQjHJ GdJYGed eY GdMOK (BObJECT MODELs
Keywords: (3GdMhGSjHs; (3THcGJ GdMhGSjHs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s